The Effect Of Social Media Promotion And Word Of Mouth On The Decision To Visit The Attraction Of Tanjung Bias Beach, West Lombok Regency - Masyhudi, Lalu; Utama, Lalu Satria; Chelsania, Ni Putu Ajeng; Susanty, Sri; Murianto, Murianto; Purwata, I Ketut (Jurnal Manajemen Industri dan Logistik, 2024)
This study aims to determine the effect of promotion through social media and word of Mouth on visiting decisions with the control variables of attractiveness and facilities. The data collection technique used a questionnaire that had been tested for validity and reliability. Based on the simultaneous hypothesis testing, the four independent variables have a significant effect on the decision to visit tourists to Tanjung Bias Beach. Partially, word of mouth (X2) has a positive and significant effect on the decision to visit tourists, this can be seen from the t-count value of 5.816, greater than the t-table value of 1.995. Social media promotion (X1), Attraction (X3) and Facilities (X4), and show that the result of the multiple linear determination coefficient (R2) is 0.648, or 65%. This means that the degree of influence of the independent variable (X) on the variable (Y) is 65%.